Dereplication of natural products using minimal NMR data inputs. Issue 39 (18th September 2015) - Williams, Russell B.; O'Neil-Johnson, Mark; Williams, Antony J.; Wheeler, Patrick; Pol, Rostislav; Moser, Arvin
Abstract : A strategy for the dereplication of a complete and a partial structure using 1 H NMR, 1 H– 13 C HSQC and 1 H– 1 H COSY spectral data, a molecular formula composition range and structural fragments against a massive database of about 22 million compounds is considered. Abstract : A strategy for the dereplication of a complete or a partial structure using 1 H NMR, 1 H– 13 C HSQC and 1 H– 1 H COSY spectral data, a molecular formula composition range and structural fragments against a massive database of about 22 million compounds is considered. As the increasing availability of public online databases containing natural products continues to grow the potential of utilizing these resources for dereplication purposes increases. This work examines approaches for NMR dereplication of natural products and includes a comparison with approaches for molecular formula and mass-based dereplication. The strategy is an application of computer-assisted structure elucidation using ACD/Structure Elucidator and data obtained from the ChemSpider database hosted by the Royal Society of Chemistry.